Enhancing Medical Imaging with Swarm Intelligence Algorithms - Pastor Reglos Arguelles Jr; Maka Jish- kariani (Wasit Journal of Computer and Mathematics Science, 2023)
Medical imaging serves as an indispensable tool for the diagnosis and continuous monitoring of a diverse array of health conditions. A recent and exciting development in this field is the integration of Swarm Intelligence (SI) algorithms, which draw inspiration from the collective behaviors observed in social insects. This collaborative effort between nature and technology is progressively transforming medical image analysis, elevating both its quality and efficiency. In this book chapter we have presented various SI optimization algorithms like ACO, BCO, FA, FSA and WOA in detail. By exploring these algorithms, we aim to provide an in-depth understanding of their respective benefits and limitations when applied to medical image analysis. This knowledge empowers practitioners to choose the most appropriate algorithm for specific tasks, ensuring optimal outcomes. Furthermore, we shed light on SI-Based Segmentation methodologies, elucidating the advantages and constraints associated with these approaches. The ability of SI algorithms to innovate in the realms of image segmentation, feature extraction, and classification is emphasized, with a focus on their potential to enhance diagnostic accuracy and elevate the quality of patient care. One of the most exciting prospects on the horizon is the amalgamation of SI with cutting-edge technologies like deep learning and big data analytics. This union has the potential to revolutionize medical imaging by providing solutions that are not only more accurate and efficient but also highly clinically relevant. As these developments continue to unfold, the synergy between SI and emerging technologies promises to reshape the medical imaging landscape, ultimately enhancing patient care and improving healthcare outcomes in unprecedented ways